Film drainage and the lifetime of bubbles. (17th September 2013) - Nguyen, C. T.; Gonnermann, H. M.; Chen, Y.; Huber, C.; Maiorano, A. A.; Gouldstone, A.; Dufek, J.
<x xml:space="preserve">Abstract</x> [1] We present the results of new laboratory experiments that provide constraints on inter bubble film thinning and bubble coalescence as a consequence of liquid expulsion by gravitational and capillary forces. To ensure dynamic similarity to magmatic systems, the experiments are at small Reynolds numbers <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4t84dvwn" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />(Re≪1)</alternatives> and cover a wide range of Bond numbers (10−3 ≤ Bo ≤ 102). Results indicate that at Bo < 0.25 film drainage is due to capillary forces, whereas at Bo > 0.25 gravitational forces result in film thinning. The film drainage time scale is given by t ∼ C ln (α) τ and is orders of magnitude faster than often assumed for magmatic systems. Here, C ∼ 10 is an empirical constant and α is the ratio of initial film thickness to film thickness at the time of rupture and τ is the characteristic capillary or buoyancy time scale at values of Bo < 0.25 and Bo > 0.25, respectively.